Aplikasi Perhitungan Gaji Karyawan CV.FRICI Berbasis Desktop Menggunakan Vb.Net & Ms.Access - Ahmad Rais Ruli (Jurnal Khatulistiwa Informatika, 2017)
ABSTRACTEvery company or institution needs a data processing application system and employee salary calculation. CV. Frici is a company engaged in the garment. Currently the company only uses Microsoft Excel applications in the process of calculating the salaries of employees and data storage is still in the form of archives, this causes the payroll process to be less effective and there are still errors in the process. Based on the explanation will be made an employee salary calculation application CV. Frici desktop-based. In making the application is used VB.NET programming language and Microsoft Access database applications. Making this application aims to facilitate the process of data addition, data conversion, data deletion and employee salary calculation becomes more effective and efficient and accurate.Keywords : VB.NET, Ms access, Ms Excel.